Feasibility of drug delivery to the eye's posterior segment by topical instillation of PLGA nanoparticles - Kohei Tahara; Keiichi Karasawa; Risako Onodera; Hirofumi Takeuchi (Elsevier, 2017)
We investigated the delivery of drugs to the posterior segment of the eye by non-invasive topical instillation using submicron-sized poly(D,L-lactide-co-glycolide) (PLGA) nanoparticles (NPs). Surface-modified PLGA NPs were developed to improve the drug delivery efficiency to the retina and were administered as topical eye drops to mice. Chitosan (CS) and glycol chitosan (GCS), which are mucoadhesive polymers, and polysorbate 80 (P80) were used as surface modifiers, and have been reported to increase the association of NPs with cells. Coumarin-6 was used as a model drug and fluorescent marker, and after ocular administration of PLGA NP eye drops, the fluorescence intensity of coumarin-6 was observed in the retina. The fluorescence image analysis indicated that there are several possible routes to the retina and fates of PLGA NPs in ocular tissue, and that these pathways involved the corneal, non-corneal, or uveal routes. Delivery to the mouse retina segments after topical administration was increased by surface modification with CS, GCS, or P80. Surface-modified PLGA NPs are a promising method for retinal drug delivery via topical instillation.